Brand Positioning Strategy in Increasing the Competitiveness of Local Products - Mubarok, Teten Mohamad Sapril; Setiawan, Rahayuniati; Maulani, Galih Abdul Fatah; Hamdani, Nizar Alam; Dahlena, Alni; Isnawati, Isnawati; Adiansyah, Adi (Jurnal Inovasi Bisnis dan Kewirausahaan, 2024)
Opportunities for local products to innovate in how they position themselves in the market, making innovation part of a strong brand identity. Local products are considered superior in terms of natural product content, after-sales service and easy to find/available in the market. The purpose of this study is to identify that product differentiation is also important to build a strong brand image. The systematic reviews and meta-analyses research method is an effective way to go beyond the traditional limitations of literature studies, allowing researchers to gain increased competitiveness of local products. The results of this study identified that brand positioning with the competitiveness of local products has grown quite significantly. By understanding consumer behavior and emerging market trends, companies can adjust their marketing strategies and leverage a combination of conventional and digital marketing channels to increase local brand visibility and competitiveness. Therefore, optimal brand positioning can increase the competitiveness of local products.